Hegemonic tool? nationalism in Philippine history textbooks, 1900-2000 - Curaming, Rommel A. (Philippine studies : historical and ethnographic viewpoints, 2017)
"This stud analyzes fifteen history textbooks published from 1905-2000 to identify patterns of nationalist discourses relating to: (1) membership in the nation; (2) origins of the people; (3) national self-image; and (4) hero and heroism as exemplified by José Rizal. It finds that, across time and thematically within a given period, the patterns of discourses are generally incoherent, which indicate that the control over official history knowledge production has been less than hegemonic. Apart from weak policy implementation, this study suggests that textbooks embody a plurality of competing social forces and reflect the political dynamics of an era."